RANCANGAN KESEHATAN DAN KESELAMATAN KERJA PADA GEDUNG KULIAH BARU TOWER B. INSTITUT AGAMA ISLAM NEGERI (IAIN) DENGAN METODE OHSAS 18001 - Taufiq, Rahmad; Indrayadi, M.; Wardhani, Nurul (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
In the construction industry workplace accidents can happen anytime. This is because the construction industry has heavy work characteristics and has a high accident risk for workers, ranging from materials used, equipment, and work environment. Accidents occurring in construction projects are mostly due to inexperienced workers on what they do, equipment that is not feasible to use, unsafe working environment conditions, the behavior of employees who are less concerned about safety, the management of companies that are less concerned about safety, unsafe working methods, and poor supervision of workers. Workplace accidents occurring in construction projects may result in direct and indirect losses. Direct losses, for example, injury to labor and damage to production facilities, then indirect losses such as losses due to cessation of production processes, production decline, claims or compensation, social impact, image and consumer confidence. Therefore, the health and safety system issues in a construction project should be well planned, in addition to ensuring that workers feel safe and secure, will also reduce the large expenses of the company as a result of workplace accidents. In the construction of the new college building Tower B. State Islamic Institute (IAIN) Pontianak 2016, created a design of health and safety (OHS) by the method of OHSAS 18001 which begins by conducting accidental analysis that may occur, and the cause of the accident of three the main factors are human factor, occupation factor and implementation method, and environmental factor, from the result of analysis of the three factors can be planned each of the prevention efforts, then proceed with making activity schedule plan and use of K3 tool adjusted to project schedule, then an evaluation of the application of OSH procedures during the project activities takes place, this evaluation aims to control and ensure that the OSH procedures are developed, in accordance with what has been planned.Keywords: K3, Accident, Loss, Method of OHSAS 18001